Antimicrobial activity of antimicrobials against extended-spectrum .BETA.-lactamase (ESBL) in Escherichia coli - Muratani Tetsuro; Kobayashi Tomoko; Gotoh Ryoko; Wada Akiko; Arima Suminori; 大隈 雅紀; Yakushiji Hiroko; Odahara Yuko; Shigetaka Masayuki; Ohkubo Kohei; Yamada Yoji; Matsumoto Tetsuro (Japanese Journal of Chemotherapy, 2004)
We studied the antimicrobial activity of 42 antimicrobial agents against 143 Escherichia coli isolates identified structural gene of extended-spectrum β-lactamase. The 143 isolates were from 133 patients who visited 31 hospitals in northern Kyushu and Yamaguchi. ESBL items were UOE-2 (CTX-M-14 or-18) type 34, CTX-M-2 type 43, CTX-M-3 type 17, UOE-1 type (CTX-M-15) 24, CTX-M-12 type 3, SHV-12 type 20, and TEM type 2. Against UOE-2 and CTX-M-2 ESBL producing isolates ceftazidime, cefepime, and aztreonam showed comparatively low MIC, and against TEM and SHV type ESBL producing isolates cefotaxime, cefpirome, and cefepime showed comparatively low MIC. Against all ESBL producing isolates, most cephalosporins and penicillins showed high MIC. Carbapenems (imipenem and meropenem) were the most active of all agents tested. The growth of all isolates was inhibited at 0.25μg/mL of meropenem and 0.5μg/mL of imipenem. Cephamycins, which have methoxy substitute at position 8, also have good activity against ESBL producing E. coli. Cefmetazole had a resistant, and latamoxef and flomoxef were susceptible against all isolates. Regarding β-lactam combined with β-lactamase inhibitor, against CTX-M type ESBL producing isolates piperacillin/tazobactam showed good activity than cefoperazone/sulbactam, while against TEM and SHV type ESBL producing isolates cefoperazone/sulbactam showed good activity than piperacillin/tazobactam. Although the activity of ampicillin/sulbactam and amoxicillin/clavulanic acid improved compared to ampicillin and amoxicillin alone, the improved MIC was not less than the breakpoint MIC. Regarding non-β-lactams, quinolones (ciprofloxacin, levofloxacin, and gatifloxacin), tetracycline, gentamicin, and cotrimoxazole showed less activity, while minocycline and fosfomycin were susceptible more than 75% against ESBL producers except UOE-2 producers. Early detection of ESBL producers and early infection control are vital importance to preventing ESBL producer outbreaks. 1998～2004年までの間に九州・山口地区で分離された基質特異性拡張型β-lactamase (ESBL) 産生Escherichia coliのうち, 31施設133人から分離され, ESBLの構造遺伝一子まで決定された143株を用い, 各種薬剤の抗菌力を検討した。ESBLtypeの内訳は, UOE-2 (CTX-M-14, -18) type34, CTX-M-2type43, CTX-M-3type17, UOE.1 (CTX-M-15) type24, CTX-M-12type3, SHV-12type20, TEM type2株であった。UOE-2およびCTX-M-2type産生株に対しては, ceftazidime, cefepimeおよびaztreonamが, TEMおよびSHV typeに対してはcefotaxime, cefpiromeおよびcefepimeのMICが比較的低い値を示したが, cephalosporinsおよびpenicillinsのMICは高く, 特に経口薬のMICはそれぞれのbreakpoint MICと比較して高い値を示した。Carbapenemsの抗菌力が最も強く, meropenemは0.25, imipenem0.5μg//mLですべての株の発育を阻止した。8位にmethoxy基を有するcephamycinsの抗菌力も強く, latamoxefは8μg/mLで, flomoxefは4μg/mLですべての株の発育を阻止し, cefmetazoleは, 1株32μg/mLを示す株が存在したが, その他は, そのbreakpointMICである16μg/mLで発育を阻止した。β-lactamase阻害薬との合剤では, CTX-Mtypeに対しては, piperacillin/tazobactamが, TEMおよびSHVtypeではcefoperazone/sulbactamの抗菌力が強かった。Ampicillin/sulbactamおよびamoxicillin/clavulanicacidはそれぞれの単剤よりも明らかにMICは改善されたが, Breakpoint MIC以下とならない株が多数存在した。β-lactams以外では, quinolones, tetracycline, ST合剤およびgentamicinの感受性率は低く, minocyclineおよびfosfomycinはUOE-2 typeを除いて, 75%以上の感受性率を有していた。ESBL産生菌に有効な薬剤は限られており, また院内感染により拡がりやすい耐性菌であるため, 早期検出, 早期対策を行う必要がある重要な耐性菌である。